Territorio y cultura: una mirada al trabajo infantil en el sector rural, San Eduardo, cantón Echeandía, provincia Bolívar, 2021. - Dorado Carrera, Evelyn Jackeline (2023)
The present investigation is carried out with the intention of finding solutions to the problem that is going to be mentioned below, child labor, is a global problem and at the same time local, on this occasion the rural sector has been selected to analyze in this study, The research specifically focuses on why child labor in the rural sector is not considered as such? But rather it is totally naturalized and it is believed that it is normal for children to put aside their things to help their parents work in order to generate money and be able to survive, with this research it is sought to demonstrate that effectively in the rural sector it is practiced child labor unconsciously, disguising this as a process of enculturation in which parents teach more traditions to their children, just as they were taught by their parents generation after generation, then it is from here that the research question arises, why child labor is considered a cultural practice in the rural sector of the San Eduardo compound, Echeandía canton, Bolívar province? the bibliographic review, interviews and observation participated as application techniques in the population of sample that was chosen, obtaining results that allowed accepting the hypothesis initially raised, since with the interviews the parents referred things that could not be detected in the observation sheets, and effectively unconsciously and without intention of harming their children, the parents are practicing child labor on their children. For which it is recommended that state and NGO support be sought so that more in-depth research is carried out within the rural sector and thus support projects are created in it so that families do not have the need to make children.